Philanthropy in practice: pragmatism and the impact of philanthropic action - Thümler, Ekkehard (Routledge studies in the management of voluntary and non-profit organizations, 2017)
Acknowledgements -- Introduction: contemporary philanthropy and its problems -- Theory -- Pragmatism and the evolution of intelligent social action -- Mapping the space of social problems -- A contingency model of problem solving strategies -- The role of niches in processes of (social) innovation -- Case studies -- The chance: opening the doors to the labour market for disadvantaged youth -- Foundation interkultur and the intercultural garden movement : catalyzing emerging practice at the grassroots -- The nuffield foundation and the Nuffield Council on Bioethics : organizing the provision of nonpartisan expertise -- The Joseph Rowntree Charitable Trust and the campaign for freedom of information : campaigning for access to files -- Analysis -- From experimentation to exploration: the pragmatic model of action in philanthropic practice -- Explanations for social impact : the door opener mechanism -- Towards a model of philanthropic niches and intelligent niching -- Conclusion and outlook -- Appendix A: List of cases -- Appendix B: Interview schedule -- References